De-privatisation and remunicipalisation of urban services through the pendulum swing: Evidence from Germany - Weber, Gabriel; Cabras, Ignazio; Frahm, Lars-Gunnar (Journal of Cleaner Production, 2019)
This paper explores and examines the distribution of environmental conflicts in Germany between 1985 and 2015, analysing the main causes for environmental conflicts related to privatisation and de-privatisation processes of urban services in 80 German cities. Using information collected via means of a Delphi Method based on focus groups with experts, we identify 90 cases of large-scale privatisation initiatives involving urban services occurred in different fields within the period considered. In 38 cases, privatisation was reversed due to initiatives undertaken by environmental justice organisations and other local grassroots groups promoting de-privatisation and re-municipalisation. In another 30 cases, privatisation was prevented as a result of these initiatives. Findings from our analysis indicate that de-privatisation initiatives and potential conflicts related to them are frequently driven by grassroots organisations promoting the provision of commons-based urban services. Our findings also suggest that privatising services in the energy, water supply and waste management sectors is likely to negatively affect the quality of service supply and increasing prices for urban residents. Image 1 • This paper explores ecological conflicts in Germany by using comparative analysis, statistics, and political ecology. • It investigates the main causes for conflicts related to privatisation and de-privatisation of urban services. • With a Delphi Method and focus groups with experts, we identify 90 cases of large-scale privatisation. • 38 initiatives of de-privatisation are identified, many driven by grassroots organizations reclaiming the concept of commons. • De-privatisation initiatives indicate a pendulum swing towards more socially controlled production.
Keywords: Delphi method; Germany; Polanyi's pendulum; city dwellers; environmental justice; pendulums; political ecology; privatisation and de-privatisation; remunicipalisation; services and utilities; sustainable cities; urban areas; water supply management

Islam, entrepreneurship, and embeddedness - Tok, M. Evren; Kaminski, Joseph Jon (Thunderbird International Business Review, 2019)
This study centers on the premise that entrepreneurship is an embedded process. Although "the entrepreneur" is inherently an "individual," entrepreneurship can never be fully disembedded from the more general social settings within which any business venture is situated. An Islamic‐based economic discursive framework should be cognizant of the different forms of sociality, spatiality, and community as well as the various norms, codes, and symbols that define society more generally. The work of Karl Polanyi on embeddedness is engaged and juxtaposed with Islam's understanding of the ideal mode of economic discursive practices. Islamic economic models and Polanyi are both critical of the corrosive effects of unbridled capitalism and individualism that ultimately lead to reification and exploitation. The conclusion recommends more small‐N case studies by researchers and entrepreneurial educational materials that emphasize the importance of networks and local embeddedness.
Keywords: Islam; POLANYI, Karl, 1886-1964; discursive practices; economic models; entrepreneurship; teacher researchers

State Capitalism Revisited: A Review of Emergent Forms and Developments - Dolfsma, Wilfred; Grosman, Anna (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Even when the neoliberal ideology of the free market was more dominant than it now is, the state was involved in economic activities that could be undertaken by private firms. State capitalism takes increasingly diverse forms, including beyond direct, partial or even indirect ownership. This paper briefly reviews some of these forms without claiming to be exhaustive as the shape state capitalism takes differs widely across the institutionalized contexts of countries. We assess state capitalism using Polanyi's double movement framework and argue that this framework needs adaptation to novel forms of state capitalism that include, e.g., state-owned multinationals and sovereign wealth funds.
Keywords: SOMNCs; capitalism; double movement; economic development; economic systems; international relations; investments; profit; sovereign wealth funds; state capitalism; state-owned enterprises

Financialization, Class Interests, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Many observers expected a stronger countermovement against neoliberalism following the Great Recession. This article argues that such a protective response failed to materialize because the financialization process has aligned the preferences of labor and rentier classes. The result has been weaker support in democracies for expansionary monetary and fiscal policies during the early stages of recessions, which further lowers aggregate spending by increasing uncertainty. Thus, reversing the culture of financialization may be a necessary condition for preventing and responding to financial crises.
Keywords: Polanyi, Karl, 1886-1964; business development; double movement; economic development; economic policy; financial crises; financialization; macroeconomic policy; monetary policy

Karl Polanyi on Strategy: The Effects of Culture, Morality and Double-Movements on Embedded Strategy - Faulconbridge, James; Muzio, Daniel (Social Science Research Network, 2019)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market. KM: from forthcoming book "Critical perspectives on Accounting"
Keywords: double movement; embeddedness; professional services; strategy